A model for the Guaraní expansion in the La Plata Basin and littoral zone of southern Brazil - Bonomo, Mariano (2015)
Since the 19th century, it has been proposed that the wide geographic distribution of the Guaraní indigenous populations in large areas of South America was the result of prehistoric movements of large numbers of people through the main rivers of the La Plata Basin and the Brazilian coastline. However, no detailed spatial and temporal analysis has been carried out with the dated Guaraní archaeological sites of the different zones of Brazil, Argentina, and Uruguay. This is one of the reasons why some of the main ideas about this past population expansion still lack empirical validation. This paper presents a study on the geographic and temporal distribution of the Guaraní archaeological sites in the La Plata Basin and the Atlantic coast of southern Brazil. The overall purpose is to contribute to understanding the Guaraní expansion using the analysis of two basic archaeological variables: space and time. Based on available numerical dates (14C and thermoluminescence) and the application of GIS software, potential dispersion routes are discussed. To date, more than 1100 archaeological sites assigned to the Guaraní, along with almost 250 numerical dates were analyzed. With this data, it was possible to elaborate a Dispersion Routes Model and a Temporal Visualization Model, which enabled identification of the sequence of population dispersal, with two main expansion pulses, throughout nearly two millennia of Guaraní movements across the South American Lowlands.